If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y(y) + 14y + 13 = 0 Multiply y * y y2 + 14y + 13 = 0 Reorder the terms: 13 + 14y + y2 = 0 Solving 13 + 14y + y2 = 0 Solving for variable 'y'. Factor a trinomial. (13 + y)(1 + y) = 0Subproblem 1
Set the factor '(13 + y)' equal to zero and attempt to solve: Simplifying 13 + y = 0 Solving 13 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + y = 0 + -13 Combine like terms: 13 + -13 = 0 0 + y = 0 + -13 y = 0 + -13 Combine like terms: 0 + -13 = -13 y = -13 Simplifying y = -13Subproblem 2
Set the factor '(1 + y)' equal to zero and attempt to solve: Simplifying 1 + y = 0 Solving 1 + y = 0 Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + y = 0 + -1 Combine like terms: 1 + -1 = 0 0 + y = 0 + -1 y = 0 + -1 Combine like terms: 0 + -1 = -1 y = -1 Simplifying y = -1Solution
y = {-13, -1}
| X+.5+.25=2.75 | | 7c(5-2c^2+c^3)= | | x-(x*(20/100))=120 | | .75-x=10.45 | | 9m-3=6 | | 3(2y+4)=12y-12 | | 1.4n=2n+3.2 | | 8y=24-6x | | m=n-p/r-5 | | X+.4=.7 | | 7U=12 | | 1.4(-2)=2(-2)+3.2 | | 4a^2+52a-120=0 | | -16t(t)+8t-8=0 | | 66*6= | | 4*(3*1)=5y+66 | | 5/8n=1/4 | | 3x^2+2y^2+12x-4y+8=0 | | 19.40+0.75(450-100)= | | 11+5x=4x+20 | | x-.875=.25 | | 5x+5-6(x+1)=3x-1 | | 100-[(8*5)+20]=40 | | 7/(7x) | | 2x^2-3x-100=0 | | 3=3x-14 | | -5+4(x+4)=(x+4) | | 7/7x | | 2/5y=13/5y | | 2x=-74x | | 87+67= | | 32=-16t(t)+8t+24 |